Estudar e ensinar literatura infantil na educação com base em nova metodologia - Ismayilova, Nezaket (Revista EntreLinguas, 2022)
In this scientific article we have studied the literary heritage in the light of a new modern national thinking, in accordance with the requirements of the time. In addition to traditional materials in the teaching of children's literature, the latest scientific achievements in this field were highlighted, and the need for works that fully reflect the child's inner feelings, joys, sufferings, psychological and spiritual experiences was shown. In the process of teaching, in the formation of the spiritual education of children and youth, in terms of expanding their worldview, the study of children's literature in education in the direction of the latest methodology is set as an important issue of today. In order to train specialists who can meet these requirements, it is necessary to revise the curriculum, programs, textbooks, teaching aids in higher education, and their level should be set at the level of today's requirements, both in terms of teaching methods and scientific theory.